Abstract Compositions on Ceramics in the Art of the Pazyryk Culture - Grigoryeva, Alina N. (Actual Problems of Theory and History of Art, 2023)
On the territory of the Pazyryk culture, an extensive body of ceramics painted with abstract compositions of geometric motifs was found in several burial complexes of the 6th–3rd centuries B.C. It has been repeatedly noted in the historiography that the motifs of abstract compositions on ceramics are characteristic of Pazyryk art. However, the question of the compositional principles of abstraction and their connection with the ornamental compositions of Pazyryk art have remained outside the scope of research. This article considers abstract compositions on ceramics in the context of the formation and development of a general trend towards abstraction characteristic of the art of the Pazyryk culture. In the course of the study, painted ceramics are compared with materials of the Central and Mountainous Altai of the 6th–4th centuries B. C.: items from the burial grounds of Balyk‑Sook‑I, Bashadar 2, Tuekta 1, 2, Pazyryk. It is the ceramic complexes that make it possible to reconstruct the main lines of the development of abstract ornamental compositions in the early Pazyryk period and to reveal the origins of artistic techniques and methods in the art of the Bashadar and Tuekta mounds, which finalizes that period. As a result of the study, the main compositional techniques that are characteristic and universal for different types of Pazyryk art throughout the history of its development have been determined, and the existing classification of ornamental motifs in the art of the Pazyryk culture has been clarified.